2009
DOI: 10.1007/s10916-009-9403-5
|View full text |Cite
|
Sign up to set email alerts
|

Critical Elements and Lessons Learnt from the Implementation of an RFID-enabled Healthcare Management System in a Medical Organization

Abstract: Healthcare services are complex and life-critical. One mistake in any procedure may lead to irremediable consequences; numerous researchers, thus, introduce information and communication technology to improve quality of services and enhance patient safety by reducing the medical errors. Radio frequency identification (RFID) is considered as one of the emerging tool assist in meeting the challenges of the present situation. In recent years, RFID has been applied in medical organizations for the purpose of manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 23 publications
1
60
0
Order By: Relevance
“…Data security, in the healthcare environment, is one of the concerns regarding adoption of a health information systems [116], [117]. According to Lin et al [106], information security and accuracy should be taken into consideration by the healthcare provider, attempting to punish any possible errors.…”
Section: His Security Concernmentioning
confidence: 99%
“…Data security, in the healthcare environment, is one of the concerns regarding adoption of a health information systems [116], [117]. According to Lin et al [106], information security and accuracy should be taken into consideration by the healthcare provider, attempting to punish any possible errors.…”
Section: His Security Concernmentioning
confidence: 99%
“…They also described critical success factors and concluded that RFID technology in healthcare is still in its infancy, compared with RFID in other areas of application. Regarding implementation, Ting et al 14 reported that most of the literature focuses on the benefits of RFID in healthcare, with little attention to project management issues. Their paper provides a case study that illustrates the developmental framework and 23 critical issues in the preparation, implementation, and maintenance of an RFID project.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ngai et al [11] focus on how RFID technology can be applied for building a healthcare management system, yet it is only implemented in a quasi-real world setting. Ting et al [13] also focus on the application of RFID technology to such a project, from the perspective of its preparation, implementation and maintenance.…”
Section: State Of the Artmentioning
confidence: 99%